The Elizabethan parish in its ecclesiastical and financial aspects, by Sedley Lynch Ware, - Ware, Sedley Lynch
Johns Hopkins University studies in historical and political science under the direction of the Departments of history, political economy and political science, series XXVI, Nos. 7-8